Black Atlantic Religion : Tradition, Transnationalism, and Matriarchy in the Afro-Brazilian Candomblé - Matory, James Lorand (Book collections on Project MUSE., 2005)
Candomble is an Afro-Brazilian religion with major counterparts in Nigeria, Benin, Haiti, Cuba, Trinidad and the US, utilising sacrifical rituals and spirit possession to persuade the gods to empower and defend their followers.